P10.20.A Mechanisms of synergistic glioma growth suppression by radiotherapy and MET inhibition. (5th September 2022) - Silginer, M; Papa, E; Szabo, E; Vasella, F; Pruschy, M; Stroh, C; Roth, P; Weiss, T; Weller, M
Abstract: Background: Glioblastoma remains to be one of the most lethal solid cancers. Despite multi-modal therapy including surgery as safely feasible, radiotherapy and chemotherapy with the alkylating agent temozolomide, the median survival of affected patients is still limited to approximately one year on a population level. Thus, novel therapies are urgently needed. There is increasing interest in the role of the HGF/MET pathway in the response of glioblastoma to radiotherapy since MET may be involved in radioresistance via proinvasive and DNA damage response pathways. Material and Methods: Here we assessed the role of the MET pathway in the response to radiotherapy in vitro and in vivo in syngeneic mouse glioma models and explored potential modes of action responsible for the synergistic effects of MET pathway inhibition and irradiation on tumor growth in vivo. Results: Murine glioma cells express HGF and MET and show increased MET phosphorylation upon exposure to exogenous HGF. In vitro, glioma cell viability and proliferation are not affected by pharmacological MET inhibition using tepotinib or genetic MET inhibition using CRISPR/Cas9-engineered Met gene knockout and sensitization to irradiation by MET inhibition is not seen. In vivo, the combination of MET inhibition with focal radiotherapy mediates prolonged survival of syngeneic orthotopic glioma-bearing mice compared with either treatment alone. Complementary studies demonstrate that synergy is lost when gliomas are established and treated in immunodeficient mice, but also if MET gene expression is disrupted in the tumor of wildtype mice. Combination therapy suppresses a set of pro-inflammatory mediators that are upregulated by radiotherapy alone and which are positively regulated by transforming growth factor (TGF)-β. In line with this data, ex vivo analysis of mouse brains reveal increased TGF-β pathway activity upon irradiation alone that is counteracted by concomitant MET inhibition. Conclusion: In summary, we demonstrate synergistic suppression of syngeneic glioma growth by irradiation and MET inhibition that requires MET expression in the tumor as well as an intact immune system. Clinical evaluation of this combined treatment approach in newly diagnosed glioblastoma is warranted.